2017
DOI: 10.1097/md.0000000000006398
|View full text |Cite
|
Sign up to set email alerts
|

The expression and clinical relevance of PD-1, PD-L1, and TP63 in patients with diffuse large B-cell lymphoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 36 publications
10
63
0
1
Order By: Relevance
“…PD‐L1 protein and mRNA expression levels were significantly related to COO with higher PD‐L1 expression in patients with non‐GC type LBCL compared with patients with GCB type. This finding is a reproduction of results from three previous studies . However, as explained above, our study cohort was enriched by MYC and DH patients, which applies a selection bias, and, therefore, the cohort may not be fit to investigate the distribution of COO.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…PD‐L1 protein and mRNA expression levels were significantly related to COO with higher PD‐L1 expression in patients with non‐GC type LBCL compared with patients with GCB type. This finding is a reproduction of results from three previous studies . However, as explained above, our study cohort was enriched by MYC and DH patients, which applies a selection bias, and, therefore, the cohort may not be fit to investigate the distribution of COO.…”
Section: Discussionsupporting
confidence: 64%
“…We investigated the relationship between PD‐L1 expression and MYC and DH translocation and found a negative association between PD‐L1 expression levels in tumour cells and the presence of MYC and DH translocation in patients with LBCL. We aimed at investigating this relationship in order to achieve more consistent results as studies on PD‐L1 expression in LBCL up until now are few and show inconsistent results . Treatments targeting the PD‐L1/PD‐1 pathway has been successfully introduced in treatment of Hodgkin lymphoma and some solid cancers, but results are sparse regarding the effect of treatment in LBCL, and as PD‐L1 expression in tumour cells seems to predict outcome to treatment in Hodgkin lymphoma, it may do the same in LBCL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that four cases (44.4%) were PD‐L1‐positive. Expression of PD‐L1 in DLBCL has been previously reported and is associated with overall poor prognosis . IVLBCL in general has a poor outcome, except for the cases limited only to the skin .…”
Section: Discussionmentioning
confidence: 93%